2018
DOI: 10.1177/0969733018783222
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of slow codes by nurses working on internal medicine wards

Abstract: Nurses should be educated about the legal and ethical implications of slow codes, and qualitative and quantitative studies should be conducted that further investigate its implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(66 reference statements)
0
5
0
1
Order By: Relevance
“…In regard to pretended care to convince families that all care was performed, this has been reported during CPR in other studies. 60,61 Study findings also revealed specific ethical challenges in the field of post-resuscitation care, which were disclosure of information, withdrawing care, and withholding therapy. Participants felt the disclosure of information to patients' family members is stressful and a source of ethical conflict, and that nurses can be hesitant to provide information.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In regard to pretended care to convince families that all care was performed, this has been reported during CPR in other studies. 60,61 Study findings also revealed specific ethical challenges in the field of post-resuscitation care, which were disclosure of information, withdrawing care, and withholding therapy. Participants felt the disclosure of information to patients' family members is stressful and a source of ethical conflict, and that nurses can be hesitant to provide information.…”
Section: Discussionmentioning
confidence: 93%
“…In regard to pretended care to convince families that all care was performed, this has been reported during CPR in other studies. 60,61…”
Section: Discussionmentioning
confidence: 99%
“…How, then, does something occur that is inconsistent with legal obligations to patients and that seems so counter to ideas of compassionate and respectful care and so oblivious to the notion that there are things that medicine cannot achieve and should not do? Harms from futile CPR include disrespect for the dead individual resulting from traumatic and invasive procedures, potential harms to family members from learning that their loved one's body was subjected to these procedures, and harms to hospital staff from the moral distress resulting from participating in resuscitation efforts on someone who is dead or in “slow codes” (intentionally slow or incomplete responses to patients in cardiac arrest) 3 . So how do clinicians and hospitals arrive at the point where patients who are clearly dead, patients who have no prospect of successful resuscitation, are subjected to unequivocally futile intrusive and potentially damaging resuscitation efforts?…”
Section: Faulty Justifications For Performing Cprmentioning
confidence: 99%
“…Ein „slow code“ ist ein umgangssprachlicher Ausdruck für die irreführende Praxis, absichtlich eine suboptimale Reanimation durchzuführen, mit dem Vorwand, das Leben des Patienten zu retten. Es gibt Hinweise darauf, dass sowohl beim innerklinischen als auch beim präklinischen Kreislaufstillstand „slow codes“ durchgeführt werden, selbst wenn die Reanimation als nicht vorteilhaft für den Patienten angesehen wird [ 157 159 ].…”
Section: Evidenz Die Den Richtlinien Zugrunde Liegtunclassified